Targeted delivery of cell penetrating peptide virus-like nanoparticles to skin cancer cells - Gan, Bee Koon; Yong, Chean Yeah; Ho, Kok Lian; Omar, Abdul Rahman; Mohammed Alitheen, Noorjahan Banu; Tan, Wen Siang (http://www.nature.com/, 2018)
Skin cancer or cutaneous carcinoma, is a pre-eminent global public health problem with no signs of plateauing in its incidence. As the most common treatments for skin cancer, surgical resection inevitably damages a patient's appearance, and chemotherapy has many side effects. Thus, the main aim of this study was to screen for a cell penetrating peptide (CPP) for the development of a targeting vector for skin cancer. In this study, we identified a CPP with the sequence NRPDSAQFWLHH from a phage displayed peptide library. This CPP targeted the human squamous carcinoma A431 cells through an interaction with the epidermal growth factor receptor (EGFr). Methyl-β-cyclodextrin (MβCD) and chlorpromazine hydrochloride (CPZ) inhibited the internalisation of the CPP into the A431 cells, suggesting the peptide entered the cells via clathrin-dependent endocytosis. The CPP displayed on hepatitis B virus-like nanoparticles (VLNPs) via the nanoglue successfully delivered the nanoparticles into A431 cells. The present study demonstrated that the novel CPP can serve as a ligand to target and deliver VLNPs into skin cancer cells.